Dancing in the dark : a novel - Phillips, Caryl (Vintage Books, 2005)
In the late 1800s, when the Williams family moves from the Bahamas to the U.S., young Bert is torn between his father's insistence that he become an educated man and his own desire to perform on stage. In 1896 Bert makes a fateful decision--he decides to perform in blackface. Although accused of reviling his race, intelligent and sensitive Bert becomes the mumbling "coon," cakewalking his way to being the first black star in Ziegfeld's Follies.